Comparison of Field Ultimate Capacity (Static and Dynamic Load Test) with the Analytic Design of Bored Pile in Granular Soil, Batam, Indonesia - Kurniadhi, Rizki; Hardiyatmo, Hary Christady; Faris, Fikri (Jurnal Teknik Sipil dan Perencanaan, 2023)
A bored pile provides a large capacity obtained to toe and friction pile to support some loads such as axial, lateral, and tensile due to hydrostatic pressure or overturning moment. Static and dynamic load tests are often carried out to validate pile design before pile production in a project. This study aims to compare the ultimate capacity of the pile based on the result of static load test, dynamic load test, and pile design in granular soil of Batam, Indonesia, in which Chin-Kondner, Mazurkiewicz, Davisson, and Hansen 80% methods are utilized to obtain ultimate capacity (Qu) of static load test and dynamic test analysis apply Case Pile Wave Analysis Program (CAPWAP) method to gain ultimate capacity. The result analysis of the static load test of ultimate capacity using Chin-Kondner, Mazurkiewicz, Davisson, and Hansen 80% methods obtained results of 1379, 1300, 1375, and 1182 tons, respectively, with a Qu average of 1309 tons. A bearing capacity (RMX) of 1204 tons was obtained through a dynamic load test. Using the CAPWAP method based on the dynamic test, the ultimate bearing capacity (Ru) of 1248 tons was obtained. Analysis of pile design shows that the ultimate capacity of the bored pile in the granular soil of Batam, Indonesia, was 1157 tons. The Qu examination between field loading testing (1278.5 tons) and design pile foundation (1158 tons) was 9.4%.